Microsculpture study of Late Permian and Early Triassic conchostracans from the Babii Kamen section (Western Siberia) - E.F. Sabirova; V.V. Zharinova; F. Scholze; J.W. Schneider; I. Kogan (Учёные записки Казанского университета: Серия Естественные науки)
The microsculpture of Permian and Triassic conchostracans from the Babii Kamen section (Western Siberia) was studied in order to determine the significance of microsculpture inthe taxonomy of conchostracan species. Five types of ornamentation have been identified in conchostracans from the Permian-Triassic reference section of Western Siberia (Babii Kamen section): pitted, nodular, reticulated, radial lirae, radial fringes. The results show that several microsculpture types are common for the genus level of conchostracans. Transition from one type of ornamentation to another was noted in three species: ?Megasitum lopokolense Novojilov, 1970, “Cornia papillaria” Lutkevich, 1937, and “Concherisma tomensis” Novojilov, 1958. The observed changes in the shell microsculpture types can be considered as a taxonomic feature for these three species and should form the base for future taxonomical revisions.